The Morality of Money - Walsh, A. author. aut Link
VIII, 255 p.
Keywords: The morality of sex, violence and money is at the centre of much human life. While the first two have been subject to intensive historical and philosophical investigation, the latter has largely been neglected. The authors provide the first comprehensive introduction to the morality of money.